Sistema de creencias de alumnos acerca de su desempeño social y académico al ingresar a la universidad - Salas Blas, Edwin (2006)
This article explores the role of beliefs in students that enter university. The author claims that beliefs serve not only as determinant of the interpretation of everyday affairs but also as a source for social and personal interaction, and in the process of decision- making. Beliefs have been grouped in four: beliefs about one self and the beliefs about professors; and beliefs about peers. The data discussed in the article was obtained in a previous research conducted by the author.